Decadal and Future Simulations for Arctic Sea Ice - Casagrande, Fernanda (Novel Perspectives of Geography, Environment and Earth Sciences Vol. 4, 2023)
In this work we evaluated the ability of eleven Global Climate model belonging to CMIP5 project, focusing in the Brazilian Earth System Model (BESM-OA V2.3) results to represent the Arctic sea ice and sensitivity to CO2 forcing, using decadal simulations (1980-2010) and future scenarios (2006-2100). We validated our results with satellite observations and compared them to Coupled Model Intercomparison Project, Phase 5 (CMIP5) for the same numerical experiment [1]. BESM results for the seasonal cycle are consistent with CMIP5 models and observations. However, almost all models tend to overestimate sea ice extent in March compared to observations. By analyzing the spatial patterns, we found a systematic model error in September sea ice cover between the Beaufort Sea and East Siberia for most models. Future scenarios showed a decrease in sea ice extent in response to an increase in radiative forcing for all models. From the year 2045 onwards, all models show a dramatic shrinking in sea ice and ice free conditions at the end of the melting season. We suggested that the projected future sea ice loss is associated to a combined effect of the Arctic Polar Amplifcation and the radiative climate feedbacks processes.